Borboletas frugívoras (Lepidoptera: Nymphalidae) de Santa Maria, região central do Rio Grande do Sul, Brasil - Spaniol, Ricardo Luís (2013)
Among some factors responsible for the occurrence and distribution of species, the heterogeneity and structural complexity of the environment can be decisive to their survival. Therefore, this study aimed to characterize the fruit-feeding butterfly s guild in a transition region between the Atlantic Forest and Pampa biomes, in the municipality of Santa Maria, Rio Grande do Sul state, promoting a comparison of composition, richness, and species abundance and their association with some microclimatic variables. Between October 2011 and May 2012, monthly sampling was performed in four field areas, two associated with each biome, using the trap methodology with attractive bait of banana fermented in sugar cane juice. At the end of seven sampling occasions, 1,829 fruit-feeding butterflies belonging to 40 species and four subfamilies were captured. The richness estimator Jackknife 1 corroborated the sampled fruit-feeding butterfly richness. The areas associated with Atlantic Forest had higher species richness (S=36) compared with the areas of Pampa (S=27). Of the total richness, 23 species occurred in areas associated with the two biomes, 13 were associated solely with the Atlantic Forest ones, and four were sampled only in Pampa. Considering the abundance, 66.05% of individuals occurred in grassland sites (vegetal formation characteristic of the Pampa associated areas), and only 33.95% in forested areas (characteristic of the Atlantic Forest ones). Hamadryas epinome (C. Felder & R. Felder, 1867) and Forsterinaria necys (Godart, [1824]) showed a significant indication for the areas associated with Atlantic Forest, while Moneuptychia soter (Butler, 1877), Paryphthimoides phronius (Godart, [1824]) and Paryphthimoides poltys (Prittwitz, 1865) had indication values for Pampa associated areas. Regarding the microclimatic variables, we found an association between luminosity, temperature and relative humidity with the occurrence of most fruit-feeding butterfly s species. The results of this study reinforce the bioindication potential of the fruit-feeding butterfly s guild, due to the composition, richness and abundance patterns of this group are highly associated with environmental variation.